The Little Engine That Could - How to Start the Motor? Motivating the Online Student - Michael Eskey; Lisa Bunkowski; Kay Dennis (Park University, 2007)
Motivation is a function of initiating and sustaining goal-directed action. In addition to individual variables, student motivation is influenced by situational variables that include course design, instructional approach, and to a great extent, faculty behavior. This article presents classic literature on motivation and offers a grounded set of instructional methods and strategies with which faculty can spark and sustain motivation that leads to deep rather than superficial learning in the online learner. These classic motivational techniques have a direct relationship with today's online learner. The authors highlight the significance of external influences and describe some of the many opportunities available to faculty to enhance the motivation of online students to learn.